Defining suitable Safe System projects: The experience of the SaferAfrica project in five African countries. (December 2021) - Usami, Davide S.; González-Hernández, Brayan; Persia, Luca; Kunsoan, Noella B.; Meta, Eleonora; Saporito, Maria R.; Schermers, Govert; Carnis, Laurent; Yerpez, Joel; Bouhamed, Nesrine; Cardoso, Joao; Kluppels, Ludo; et al.
Abstract: When dealing with road safety in Africa, one should bear in mind that road safety problems need to be seen in their context as the solutions proposed to address them. While it is relevant to consider international good practices, African stakeholders should become owners of the interventions addressing their problems and take the responsibility for developing and implementing the appropriate solutions, taking advantage of suitable technical assistance, if needed. Based on these considerations, in this paper, a presentation is made of the process used in the European research project SaferAfrica to define suitable Safe System projects in Africa. This project aims at supporting policymakers and stakeholders with evidence on critical risk factors, related actions, and good practices drawn from high-quality data and knowledge. In the project, road safety and traffic management capacity reviews at the country level were carried out in five countries (Cameroon, Burkina Faso, Tunisia, Kenya, and South Africa), following the World Bank guidelines. After conducting such a capacity review, these guidelines recommend the preparation and implementation of Safe System projects, "stand-alone, multisector initiatives targeting high-risk corridors and areas, with outcomes large enough to be reliably measured." In SaferAfrica, this approach aims at facilitating the implementation of Safe System projects in the considered countries, by identifying detailed short-term improvement plans and producing contextualized terms of reference for some interventions per selected country. These interventions are remedial, they address high-priority concerns and demonstrate the viability of high potential gains within current administrative and legislative frameworks. To design interventions suitable to the existing context, the transferability audit tool was adopted within a "participative" process, involving all possible interested parties, from the institutions to NGOs. Results from the process are presented and discussed. Highlights: This study presents a methodology to transfer suitable Safe System projects in Africa. The methodology was applied in Cameroon, Burkina Faso, Tunisia, Kenya, and South Africa. The methodology allows identifying possible barriers to project implementation. The methodology adopts a participative process, involving all possible interested parties.